Use of immunostimulants and biologically active substances in fish farming - Brigida A.V.; Kitaev I.A.; Shishanov G.A. (Ветеринария и кормление)
A literature review on the use of immunostimulating additives in fish breeding has been carried out. The immunity of fish, especially in the early stages of development, directly affects survival and growth rate. And unfavorable environmental conditions: such as hydrochemical parameters of water, high temperature, low dissolved oxygen content and other factors can cause the appearance of invasive diseases and lead to the death of fish. The purpose of this study was to review the possibilities of using immunostimulating substances in aquaculture and the effectiveness of their use. The addition of biologically active substances to the diet of fish can increase productivity, give greater resistance to various diseases at the initial stages of ontogenesis, as well as improve the physiological state of the body as a whole. Many supplements not only provide better fish health, but also increase the growth rate and mass accumulation. In recent years, more and more attention has been paid to the use of plant components as immune enhancers for aquaculture facilities, replacing antibiotics and medicines.